Nahrungsanalytische Untersuchungen an einigen mitteleuropäischen Chrysopiden-Imagines (Neuroptera: Chrysopidae). - Bozsik, András (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The hind-gut contents of 1816 chrysopid adults (Neuroptera, Chrysopidae), of seven species were microscopically analyzed in order to determine their natural food. The individuals were collected in an uncultivated area (natural habitat) and a backyard orchard in Gödöll (in the north of Hungary). Pollen, yeasts, fungal spores and crystalline particles were found in considerable quantity even in species believed to be predaceous. These results suggest that adult chrysopids may have greater food diversity in nature than was previously known and according to their feeding habits the species can be divided at least into two groups: - 1. phytophagous (pollino-glycinophagous) (Chrysoperla carnea and Dichochrysa prasina). - 2. omnivorous (genus Chrysopa)- omnivorous with mainly predaceous preference but consuming also substances of plant origin in considerable quantity (Chrysopa pallens, Chrysopa viridana), - omnivorous with predominantly carnivorous preference, food of plant origin is needed only in small amounts (Chrysopa perla, Chrysopa abbreviata, Chrysopa formosa).KeywordsNeuroptera, Chrysopidae, Chrysoperla carnea, Dichochrysa prasina, Chrysopa pallens, Chrysopa viridana, Chrysopa formosa, Chrysopa perla, Chrysopa abbreviata, adults, gut content analysis, Central Europe.